Blast injury of the hand in a pediatric patient with open fracture: A case report - Nugroho, Arie; Zahra, Afifah Az; Yahya, Taufik Nur (Faculty of Medicine, Universitas Islam Indonesia, 2026)
Blast injuries can cause severe, multi-tissue damage, including open fractures and extensive lacerations. Management of pediatric hand blast injuries is particularly challenging due to a high risk of contamination and infection. We report the case of a 10-year-old boy who sustained a left-hand blast injury caused by a firecracker. The patient presented with a contaminated lacerated wound, active bleeding, tissue avulsion, and retained foreign bodies, accompanied by crepitus and cyanosis of the index finger. Initial management included debridement and irrigation. Surgical intervention consisted thorough debridement, exploration of tendon and neurovascular structure, and K-wires fixation of the index finger. Despite appropriate initial management, the patient developed chronic necrotic tissue infection, necessitating ray amputation of the index finger to control the infection. Further evaluation suggested that primary vascular disruption, exacerbated by contamination and infection, contributed to progressive necrosis, particularly at the metacarpophalangeal level. To prevent further infection spread and salvage overall hand function, repeated debridement followed by amputation at the metacarpophalangeal joint and removal of fixation wires was performed. Structured rehabilitation was subsequently initiated. Pediatric hand blast injuries represent complex traumatic conditions with a high risk of tissue necrosis. Early diagnosis and aggressive surgical management are essential; however, compromised tissue viability and severe infections may necessitate amputation as a limb-salvage strategy. This case underscores the importance of comprehensive management and highlights the need for improved community-based prevention efforts.